Efektivitas Ekstrak Alga Coklat Padina australis dalam Menghambat Pertumbuhan Bacillus cereus dan Escherichia coli - Sampulawa, Sriyati; Ode, Asmi; Hulopi, Fauzia; Nirmala, Wa; Bahalwan, Farida; Darmawati, Siti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to determine the effectiveness of the brown algae extract Padina australis in inhibiting the growth of Bacillus cereus and Eschericia coli bacteria. Samples were taken from the waters of Osi Island, West Seram, Maluku Province as much as 1 kg, the sample was then dried using the sundrying method. The dried sample was then soaked for 24 hours and extracted. The extract results were then tested for phytochemicals and antibacterial activity tests carried out in the Microbiology Laboratory of Pattimura University, Ambon. The results showed that (1) The brown algae extract Padina australis contains secondary metabolites in the form of flavonoids, terpenoids, steroids, saponins and alkaloids; (2) The combination of these various compounds provides a synergistic effect that can increase the effectiveness of antimicrobials in inhibiting the growth of Bacillus cereus and Escherichia coli bacteria; (3) The minimum inhibitory concentration (MIC) of Padina australis algae extract has different abilities in inhibiting test bacteria. The MIC of Bacillus cereus bacteria at a concentration of 10% has an inhibition zone of 7 mm and the MIC of Escherichia coli bacteria at a concentration of 60% has an inhibition zone of 11 mm.